Invited examiner of PhD dissertations : Pablo Fernández Cancelo (University of Lleida), Distant external examiner of the dissertation, Title: Deciphering the developmental and environmental cues influencing ripening and colour development in apples Advisors: Neus Teixidó Espasa, Jordi Giné Bordonaba, María Inmaculada Viñas Almenar - Manganaris, George A. (My University, 2026)
Invited examiner of PhD dissertations.
Keywords: Sciences